Neurośrodowiskowe przyczyny opóźnionego rozwoju mowy w wieku niemowlęcym - Cieszyńska-Rożek, Jagoda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The article presents the results of the experimental studies conducted so far on the devel- opment of infants’ primary communicative abilities, carried out in vivo. The findings of neurobiologists on the formation of the structures of the social brain not only influ- ence the process of early diagnosis of developmental disorders, but also allow for the construction of principles of early intervention. The article discusses the results of our own study of thirteen infants born in Poland and abroad, conducted by means of par- ticipant observation (online). The aim was to reveal the disturbances in shaping social responses in a lockdown situation and to define a pattern for preventive interventions.